La Gestión Financiera y la Sostenibilidad de las Cooperativas de Ahorro y Crédito del segmento 3 de la provincia de Loja, periodo 2019 – 2020. - Contreras Salinas, Silvia Patricia (2022)
The entities of the popular and solidarity financial system must have a deep knowledge of its operation, as well as have reliable and truthful information in order to guarantee efficient decision-making. The present research work entitled: "Financial Management and Sustainability of Savings and Credit Cooperatives of segment 3 of the province of Loja, period 2019 - 2020", had as its main objective to analyze how financial management affects the sustainability of institutions of the aforementioned segment, which allows them to operate efficiently for their growth and permanence over time. The CAMELS methodology was used to measure indicators of capital adequacy, asset quality, management efficiency, profitability level, liquidity management and sensitivity to market risk; sustainability indicators were used to analyze each of the cooperatives and their comparison with the average of segment three at the national level as an optimal indicator and the Pearson coefficient was used to evaluate the correlation of the variables under study. It is obtained as relevant results that the Crediamigo, Cristo Rey and La Fortuna cooperatives present a stable situation in their financial and administrative management, positioning the Crediamigo cooperative as the entity with the best financial performance in the segment. In addition, healthy indexes were evidenced, which allow these cooperatives to be within the financial market to which they belong, it should be noted that there is a strong correlation between financial management and sustainability. Finally, financial strategies aimed at improving decision-making in the short and long term are proposed.